0853 The role of sleep-disordered breathing in the optimization of pediatric epilepsy management. (25th May 2022) - Youssef, Nada; Gupta, Gita; Romanowski, Erin Fedak; Lewis, Toby; Hassan, Fauziya
Abstract: Introduction: There is a known bidirectional relationship between epilepsy severity and disordered sleep; however, both the potential scoring limitations of polysomnograms (PSGs) of children with epilepsy and the effect of treatment of sleep disordered breathing (SDB) on epilepsy severity in these children remain poorly understood. Report of Cases: We describe a 7-year-old male with a history of prematurity (ex-34 weeks), bronchopulmonary dysplasia, recurrent aspiration pneumonia, and refractory nocturnal epilepsy who experienced acute hypoxemic respiratory failure in the setting of co-infection with rhinoenterovirus and parainfluenza 4 virus. The patient's epilepsy history is notable for multiple nocturnal seizures most days of the week for a period of several years. His mother endorsed that the nocturnal seizures began shortly after his SDB symptoms, and that the severity of his nocturnal seizures seemed to be associated with the quality of his sleep. Two years prior to admission, he underwent adenotonsillectomy for mild obstructive sleep apnea (AHI 2.5, REM AHI 8.9, minimum SpO2 86%). He continued to have persistent SDB symptoms (e.g. witnessed apneas, nocturnal arousals 5-10 times/night, daytime sleepiness) despite adenotonsillectomy. Notably, the background EEG (in the context of epilepsy) demonstrated obscured sleep architecture and led to unreliable staging of sleep states and cortical arousals. Given the disorganized background EEG, arousal-based hypopneas could have been underestimated. In the setting of acute respiratory failure, our patient was hospitalized and treated with noninvasive ventilation for 6 days. Collateral benefits included improvements in SDB (evidenced by decreased nocturnal awakenings, lack of obstructive features) and reduction in seizure frequency. His mother noted that this hospitalization was the first time in years that her son did not experience nocturnal seizures. Conclusion: Sleep apnea can be an important modifiable factor in the treatment of pediatric epilepsy. Some PSGs of children with epilepsy may be falsely reassuring given the potential difficulty with scoring cortical arousal-based hypopneas. Therefore, careful clinical correlation should be made between nocturnal seizures and sleep symptoms, even in the context of reassuring PSG parameters. Support (If Any): Cystic Fibrosis Foundation Training Grant, AIRE grant, NIH 2T32HL110952-06